Comparative study of CuO, CuO@Ag and CuO@Ag:La nanoparticles for their photosensing properties. (16th October 2019) - Arya, Sandeep; Prerna,; Singh, Anoop; Kour, Ravinder
Abstract: In this work, the synthesis of CuO, CuO@Ag core-shell, and CuO@Ag:La nanoparticles was done by sol gel technique. The prepared nanoparticles were further characterized for their structural, morphological and optical properties. The color coordinates of PL spectra showed that CuO@Ag:La nanoparticles has much better application potential in white light emission than CuO and CuO@Ag core-shell nanoparticles. Further, the synthesized CuO@Ag:La nanoparticles were implemented for fabrication of Glass/ITO/synthesized nanoparticles/Al thin film device. The fabricated device was tested for ± 1 V bias voltage. Results verified that the behavior of the fabricated device is similar to photoresistor and shows better sensitivity towards light. Electrical characterization confirmed that the resistance of CuO@Ag:La nanoparticles based device decreases exponentially with increase in the intensity of light while the photoresponse increases. It is therefore revealed that the CuO@Ag:La nanoparticles are an efficient material for fabrication of photosensitive devices.